Charge Injection from Chronoamperometry of Platinum Electrodes for Bionic Devices. Issue 12 (1st January 2018) - Harris, Alexander R.; Newbold, Carrie; Carter, Paul; Cowan, Robert; Wallace, Gordon G.
Abstract : The chronoamperometric response of platinum under biologically relevant conditions was investigated to understand how charge transfer across the electrode-tissue interface occurs during potential pulsing. Platinum behaves as a non-ideal electrode, passing capacitance and faradaic charge. The faradaic reactions are associated with oxide formation and removal, hydrogen and anion adsorption. The capacitance charge decayed within μs while the faradaic charge decay occurred over longer times. The total charge and the ratio of faradaic to capacitance charge was seen to vary with time, potential, electrode size, oxygen concentration, electrolyte and surface cleaning method. The charge transfer mechanisms result in an accumulation of charge during multiple potential pulses, mostly reductive charge under the conditions presented here. This modifies the composition of the electrode/solution interface. An accurate understanding of charge transfer at the electrode/tissue interface must subsequently be obtained under biologically relevant conditions (an artificial perilymph with low oxygen concentration for cochlear implants electrodes and artificial cerebrospinal fluid for neural implants) and with appropriate clinical electrodes.